An Assessment of Capital Structure Influencing on Profitability: A Case of Listed Banks on the Ghana Stock Exchange - owusu, Caleb Kwasi; Garr, David Kwashie; Awadzie, David Mensah (International Journal of Business, Management and Economics, 2023)
This study aimed to examine the impact of capital structure on bank performance using data from nine listed banks on the Ghana Stock Exchange. The study utilised secondary panel data extracted from the published financial statements of these banks. Bank performance was measured using return on assets and return on equity as proxies, while the ratio of total debt to total assets served as the independent variable. Additionally, firms' age, size, and liquidity were control variables. The random effect technique was used for analysis, employing Ordinary Least Squares (OLS) and Autoregressive methods. The results indicated a positive and significant relationship between total debt to total assets, return on assets and equity. Furthermore, firms' age positively and significantly impacted the return on assets and return on equity in both models. Interestingly, the study found a negative effect of firms' liquidity on return on assets in model one, while the size of the firms had no impact on bank performance. Policymakers can encourage financial institutions to provide accessible and affordable lending options to businesses, enabling them to leverage debt effectively. This can be particularly beneficial for small and medium-sized enterprises (SMEs) that often face challenges accessing capital.